Practical and Efficient Synthesis of Polyaryl(hetaryl)-Substituted Cyclohexenones and Salicylates - Shirinian, Valerii Z.; Kavun, Alexey M.; Lvov, Andrey G.; Zavarzin, Igor V.; Krayushkin, Michail M. (Synthesis, 2017)
A new efficient method was developed for the synthesis of triaryl-substituted cyclohexenones and salicylates. The method is based on the Robinson annulation of readily available keto esters and chalcones, followed by the aromatization of the cyclohexenone moiety. The aromatization can be accomplished either by reaction with bromine in boiling chloroform or bromination with copper(II) bromide in ethanol followed by treatment with pyridine or 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). The new synthetic method was also implemented in a one-pot protocol, which in some cases resulted in higher yields of the final product compared to those obtained in the stepwise synthesis.
Keywords: cyclohexenones; salicylates; polyaryl-substituted phenols; Robinson annulation; chalcones; bromination